hi, im stuck with this boolean algebra. F = (X + Y + X . Z) . (Y +X') btw: the law A + AB = A so does A + AB' = A? thanks in advance
yes, A+AB'=A----> its telling you it does not matter what b' is change order so you can see the form A+AB F=(X+XZ+Y) (Y+X') =[(X+XZ)+Y] (Y=X') X+XZ =======> A+AB =(X+Y)(Y+X') Then could multiply out and use: XX'=0 YY=Y and look for the form A+AB=A again
A + AB = A.(1+B) = A.1 = A A + AB' = A.(1+B') = A.1 = A Anything in OR operation with 1 results 1... Your Ques. Ans . = Y